2020
DOI: 10.3390/f11101117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi on Growth and Physiological Performance of Catalpa bungei C.A.Mey. under Drought Stress

Abstract: Catalpa bungei C.A.Mey. is a common ornamental timber species. Its survival and growth are greatly affected by water scarcity in arid and semi-arid areas of Northwest China. Evidence suggests arbuscular mycorrhizal fungus (AMF) may improve plant drought resistance. However, there is limited information on the systematic effects of AMF on drought resistance in C. bungei seedlings. Here, a pot experiment was used to explore the effects of inoculation with the AMF Rhizophagus intraradices on the growth and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 102 publications
(154 reference statements)
6
39
0
1
Order By: Relevance
“…Mycorrhizal fungi have a vital impact on the composition of microbial and plant communities ( van der Heijden et al, 2015 ; Genre et al, 2020 ), and AMF symbiosis can also improve nutrient and water supply to host plants ( Parniske, 2008 ; Song et al, 2015 ; Wang, Pokharel & Chen, 2019 ; Sarmiento-López et al, 2020 ; Shi et al, 2020a ). Positive plant water relations by AMF have been demonstrated to improve plant drought resistance ( Chen et al, 2020 ) by enhancing the uptake of N and P under drought stress ( Hashem et al, 2018 ), alleviate soil water stress ( Mickan et al, 2016 ), and promote plants to deplete soil moisture to alleviate plant water stress ( Hardie, 1985 ). Many studies also suggested that AMF may promote plant growth through enhance tolerance to abiotic stress, such as drought and salinity ( Yang, Koide & Zhang, 2016 ; Xiang et al, 2016 ; Mckibben & Henning, 2018 ; Higo et al, 2019 ; Zhang et al, 2019a , 2019b ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizal fungi have a vital impact on the composition of microbial and plant communities ( van der Heijden et al, 2015 ; Genre et al, 2020 ), and AMF symbiosis can also improve nutrient and water supply to host plants ( Parniske, 2008 ; Song et al, 2015 ; Wang, Pokharel & Chen, 2019 ; Sarmiento-López et al, 2020 ; Shi et al, 2020a ). Positive plant water relations by AMF have been demonstrated to improve plant drought resistance ( Chen et al, 2020 ) by enhancing the uptake of N and P under drought stress ( Hashem et al, 2018 ), alleviate soil water stress ( Mickan et al, 2016 ), and promote plants to deplete soil moisture to alleviate plant water stress ( Hardie, 1985 ). Many studies also suggested that AMF may promote plant growth through enhance tolerance to abiotic stress, such as drought and salinity ( Yang, Koide & Zhang, 2016 ; Xiang et al, 2016 ; Mckibben & Henning, 2018 ; Higo et al, 2019 ; Zhang et al, 2019a , 2019b ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under drought conditions, amount of some important macroelements such as phosphorus (P), calcium (Ca) and microelements such as iron (Fe), manganese (Mn), nickel (Ni), copper (Cu) and zinc (Zn) (Table1) increased by mycorrhizal symbiosis. Chen et al (2020) explained these results by extraradical hyphal network formed in the soil upon AMF colonization. P and Ca are the main mineral elements for plant growth.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, the water-use efficiency is in most cases improved in colonized plants, as observed in AM poplar and in ECM pine and oak trees exposed to drought (Li L. et al, 2021;Li Y. et al, 2021). This could be related to a better modulation of stomata closure and abscisic acid concentration and signaling (Wang et al, 2017;Ouledali et al, 2018;Chen et al, 2020).…”
Section: Droughtmentioning
confidence: 87%